Persepsi dan Preferensi Mahasiswa Terhadap Jenis Tanaman yang Diinginkan untuk Ditanam di Area Kampus Universitas Victory Sorong - Pattiwael, Maya; Turot, Amatus; Wetaku, Afrida (Median : Jurnal Ilmu Ilmu Eksakta, 2025)
The management of green space on the Victory Sorong campus actually still has great potential to be improved because there are still many empty areas that have not been used. Regarding planting, students can express their opinions about the current condition of the campus environment and provide input on the types of plants they want. The purpose of this study was to determine students' perceptions and preferences regarding the types of plants that are expected to be planted in the Victory Sorong University campus area. This study was conducted from January to February 2025 at Victory Sorong University with a sample of 296 respondents from 6 Faculties. Data collection was carried out by distributing questionnaires using Google Form and interviews. Data analysis was carried out descriptively qualitatively. The results of the study showed that students of Victory University Sorong showed various perceptions about the condition of the campus environment related to the adequacy of green space, the importance of the existence of plants, the desired location for planting, and the willingness to be involved in campus greening activities. Meanwhile, the plant preferences mentioned by respondents can be grouped into shade plants, flowering plants and ornamental leaf plants, as well as fruit and medicinal plants. This shows that students not only prioritize aesthetic factors that provide visual beauty but also want shade, coolness, results that can be directly enjoyed from fruits and their benefits as TOGA so that balance can be created throughout the campus area